2021
DOI: 10.1108/jima-10-2020-0323
|View full text |Cite
|
Sign up to set email alerts
|

How education level polarizes halal food purchase decision of Indonesian millennials

Abstract: Purpose The purpose of this paper is to evaluate Indonesian Muslim millennials’ decision-making process in purchasing halal food by introducing knowledge variable into the theory of planned behavior framework and education level (EL; i.e. low vs high) as the moderating variable. Design/methodology/approach There were 400 questionnaires that were distributed to obtain responses from Indonesian Muslim millennials consumers. SmartPLS was used as the structural equation modeling approach to perform the multi-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 124 publications
(189 reference statements)
0
16
0
Order By: Relevance
“…A study pointed out that people with a higher education level were more likely to show behaviors that were compatible with social practice [9]. Previous studies have indicated the moderating effect of education level in various conditions, which included the utility of mobile apps, product purchase, health behaviors, and so forth, verifying the moderating effect of education level within the theoretical framework of TPB [10][11][12]. In this study, we introduced education level as a moderator within TPB in the context of physical activity among chronically ill patients.…”
Section: Introductionmentioning
confidence: 95%
“…A study pointed out that people with a higher education level were more likely to show behaviors that were compatible with social practice [9]. Previous studies have indicated the moderating effect of education level in various conditions, which included the utility of mobile apps, product purchase, health behaviors, and so forth, verifying the moderating effect of education level within the theoretical framework of TPB [10][11][12]. In this study, we introduced education level as a moderator within TPB in the context of physical activity among chronically ill patients.…”
Section: Introductionmentioning
confidence: 95%
“…The theory of planned behavior is frequently used to understand the behavior of Muslim consumers when purchasing halal products (Akın & Okumuş, 2021), halal meat (Sherwani et al, 2018), and halal food consumption by Gen Y (Marmaya et al, 2019). It can even be used to understand non-Muslim behavior in consuming halal food (Wibowo et al, 2022). The consumption theory can also be applied (Muflih & Juliana, 2021).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In 2018, global Muslim consumers spending on food, pharmaceuticals, and lifestyle items totaled $2.2 trillion. For millennial Muslim consumers, the demand for halal food is growing (Wibowo et al, 2022). In Malaysia, the halal product and service sector is one of the most important economic sectors (Marmaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations